1992
DOI: 10.1111/j.1745-6584.1992.tb01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the Herbicides MCPP and Atrazine under Natural Aquifer Conditions

Abstract: The potential for aerobic biotransformation of the herbicides MCPP [(+/ ‐)‐2‐(4‐chloro‐2‐methylphenoxy)propionic acid] and Atrazine [2‐chloro‐4‐ethylamino‐6‐isopropylamino‐s‐triazine] under natural aquifer conditions was investigated. A natural gradient experiment was carried out in an aerobic ground‐water zone at the Canadian Forces Base Borden, Borden, Ontario, Canada. Over 90 days, a continuous plume was created by weekly injections of the herbicides (average concentrations of 400 jug/1 each), together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…Vanderheyden et al (1997) observed rapid degradation of atrazine in sediment samples collected from the saturated zone, and the metabolites were unidentified; mineralization of [ 14 C]atrazine began after a lag phase of ∼25 days and ∼25% of the applied [ 14 C]atrazine was mineralized in 75 days. Agertved et al (1992) observed no decrease in atrazine concentrations during 74 days in laboratory microcosms of groundwater and aquifer material.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Vanderheyden et al (1997) observed rapid degradation of atrazine in sediment samples collected from the saturated zone, and the metabolites were unidentified; mineralization of [ 14 C]atrazine began after a lag phase of ∼25 days and ∼25% of the applied [ 14 C]atrazine was mineralized in 75 days. Agertved et al (1992) observed no decrease in atrazine concentrations during 74 days in laboratory microcosms of groundwater and aquifer material.…”
Section: Introductionmentioning
confidence: 90%
“…The persistence of contaminants in situ can be determined by monitoring groundwater concentrations in field transport studies. Agertved et al (1992) observed no degradation of high concentrations of atrazine (∼400 µg/L) in 96 days in an aerobic aquifer [dissolved oxygen (DO) ranging from 2.1 to 8.0 mg/L]. Widmer and Spalding (1995) observed no degradation at concentrations more typical of nonpoint source contamination [atrazine, DEA [2-amino-4-chloro-6-(isopropylamino)-1,3,5-triazine], and DIA, each at ∼3 µg/L] in 3 months in an aerobic aquifer (DO ≈6.9 mg/L).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For small particles of -l-pm diameter it varies between a few days and 4-6 weeks, but is only a few days or less than 1 day for particles with l-10-pm diameter (5). Most studies show that atmospheric input is the primary source of PAHs to sediments and soils, especially for remote sites (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%